Changes in nasal and nasopharyngeal floras after laryngectomy - Kaygusuz, I.; Karlidag, T.; Keles, E.; Yalcin, S.; Alpay, H. C.; Yakupogullari, Y. (Galenos Yayincilik, 2005)
Objectives: The aim of this work was to evaluate changes in nasal and nasopharyngeal microbial floras after total laryngectomy. Methods: Twenty patients who performed total laryngectomy and 20 voluntary patients who have same demographic characteristics with study group included to the study. Nasal and nasopharyngeal smear cultures were obtained from these groups and the microorganisms were isolated. Results: Nasal flora was detected as normal in 7 patients of study group and in 12 patients of control group. One or more microorganisms (S. aureus in five patients, beta-hemolytic streptoccoci in two patients, P. aeroginosa in two patients, Acinetobacter spp. and Candida spp. in seven patients) were isolated in 13 patients of study group. In nasal flora of control group following microorganisms were detected; Candida spp. in one patient, beta-hemolytic streptoccoc in one patient and S. aureus in six patients. While nasopharyngeal flora were detected as normal in 14 patients of control group and five patients of study group, one or more microorganisms were isolated in six patients of control group (S. aureus in one patient, beta-hemolytic streptoccoc in one patient, Klebsiella spp. in three patients and E. coli in one patient) and 15 patients of study group (S. aureus in five patients, beta-hemolytic streptoccoci in six patients, Klebsiella spp. in five patients, Acinetobacter spp. in one patient and Candida spp. in seven patients). When study group compared to control group, microorganisms which not exist in normal nasal and nasopharyngeal flora increased in study group in proportion to control group. Conclusion: The certain changes in normal nasal and nasopharyngeal floras of patients who performed total laryngectomy. Therefore, if rhinitis, sinusitis, pharyngitis vs. would be treated in patients who performed total laryngectomy, the mentioned changes in flora should be taken into consideration.
Keywords: Total laryngectomy; nasal flora; nasopharyngeal flora